Influencia de la dosificación de hidrosulfuro de sodio (nash) y el potencial de pulpa (orp) en el grado de cobre del concentrado final en la flotación selectiva de minerales sulfurosos - Bocanegra Andrade, María Alejandra (2019)
This research studied the influence of the sodium hydrosulphide (NaSH) dosage and the pulp potential (ORP) in the copper grade of the final concentrate in the selective flotation of sulphurous minerals applying the bifactorial design with three levels and two repetitions for each factor, performing a total of 18 tests as a measure to confirm the validity and reliability of the data. The variable of Sodium Hydrosulfide (NaSH) dosage was evaluated at the levels of (20, 30 and 40) g/TM, the variable pulp potential (ORP) was evaluated at the levels (-550, -600 and - 650) mV and the variable Copper grade was evaluated in percentage (%). The results indicate that the highest percentage of copper in the final concentrate is 19.53% at a dosage of 30 g/MT and at a pulp potential of -650 mV. It is concluded that the interaction of NaSH dosage and pulp potential has a significant effect on the degree of copper in the final concentrate.